Tingkat Pemahaman Petani Padi Terhadap Pengelolaan Tata Air Pada Usahatani Di Lahan Gambut Kecamatan Kubu - Erlinda Yurisinthae (Universitas Muhammadiyah Purworejo, 2021)
The key to achieving optimal land productivity and preserving land on peatlands is water management to the level of farmland. The purpose of this study was to analyze the extent of rice farmers' understanding of water management in farmland. The location of the study was carried out in Kubu Subdistrict which is a tidal flood type A/B overflow. The population is rice farmers who work near oil palm plantations. There were 60 respondents representing 6 farmer groups. Validity and reliability tests were carried out on the questionnaire used. The data analyzed are qualitative data measured using a Likert scale. Analysis of the level of understanding is carried out with the knowledge approach and the application of water systems on farmland. The analysis shows that 85% of rice farmers have a level of understanding from quite understand to very understand. This amount is very large if seen as an opportunity for human resources to develop agricultural land on peatlands. However, in terms of age, the average farmer is over 60 years old with experience in farming above 28 years. So, there is a need for counseling aimed at young farmers with experience in farming not too long ago. Counseling material should also vary by providing insights to farmers about the use of peatlands for non-rice farming.